STUDY OF TENSILE STRENGTH OF WOOD CONNECTION USING WASTE PLASTIC BOTTLES CONNECTOR AS ADDITIONAL MATERIALS OF WOOD STRUCTURAL SUBJECT. - Aprilia Dwi Lestari; Anis Rahmawati; Taufiq Lilo Adi Sucipto (Universitas Sebelas Maret, 2017)
This research was aims to know 1) whether there was a significant difference from tensile strength of wood connection with plastic bottle waste between A bottle, B, C, D, E, and F bottle, 2) plastic bottle which produced the wood connection with the highest tensile strength. This research used quantitative method of experimental approach. The population of this research were wood with the connection of plastic bottles by heating. This technique was inspired by Micaella Pedros, an England artist who first applied it known as Joining Bottles. Dimensions for tensile test parallel that was 2,5 x 2,5 x 46 cm with total 30 samples. The length of the bottle connection is 10 cm with 1 layer only. This research used quantitative method of experimental approach. Data analysis used one way anova test, 0.05 significance level with the requirement of normal data and homogeneous data. Statistical data of this research results showed 1) no significant difference tensile strength of the six plastic bottles connector. 2) The F bottle produced the highest tensile strength that was 0,622 MPa.